Simulating nearby disc galaxies on the main star formation sequence: I. Bar formation and the building of the central gas reservoir - Verwilghen, Pierrick; Emsellem, Eric; Renaud, Florent; Valentini, Milena; Sun, Jiayi; Jeffreson, Sarah; Klessen, Ralf S.; Sormani, Mattia C.; Barnes, Ashley T.; Dolag, Klaus; Grasha, Kathryn; Liang, Fu-Heng; et al. (Astronomy and astrophysics, 2024)
Past studies have long emphasised the key role played by galactic stellar bars in the context of disc secular evolution, via the redistribution of gas and stars, the triggering of star formation, and the formation of prominent structures such as rings and central mass concentrations. However, the exact physical processes acting on those structures, as well as the timescales associated with the building and consumption of central gas reservoirs are still not well understood. We are building a suite of hydro-dynamical RAMSES simulations of isolated, low-redshift galaxies that mimic the properties of the PHANGS sample. The initial conditions of the models reproduce the observed stellar mass, disc scale length, or gas fraction, and this paper presents a first subset of these models. Most of our simulated galaxies develop a prominent bar structure, which itself triggers central gas fuelling and the building of an over-density with a typical scale of 100−1000 pc. We confirm that if the host galaxy features an ellipsoidal component, the formation of the bar and gas fuelling are delayed. We show that most of our simulations follow a common time evolution, when accounting for mass scaling and the bar formation time. In our simulations, the stellar mass of 10 10M⊙ seems to mark a change in the phases describing the time evolution of the bar and its impact on the interstellar medium. In massive discs (M⋆≥ 10 10M⊙), we observe the formation of a central gas reservoir with star formation mostly occurring within a restricted starburst region, leading to a gas depletion phase. Lower-mass systems (M⋆< 10 10M⊙) do not exhibit such a depletion phase, and show a more homogeneous spread of star-forming regions along the bar structure, and do not appear to host inner bar-driven discs or rings. Our results seem to be supported by observations, and we briefly discuss how this new suite of simulations can help our understanding of the secular evolution of main sequence disc galaxies.